Exploring multidimensional determinants of medication error reporting in China: a qualitative study using the theoretical domains framework - Guo, Hui; Guo, Qian; Wang, Xiuping; Liu, Yonghong; Wang, Ze (Frontiers in Pharmacology, 2025)
ObjectiveMedication errors, defined as preventable events leading to inappropriate medication use or patient harm, remain a critical global healthcare challenge. Despite regulatory mandates in China, underreporting remains systemic. Existing research on healthcare professionals’ reporting behaviors has been constrained by reliance on isolated theoretical frameworks, which inadequately address the interplay of individual, organizational, and cultural determinants. The aim of this study is to systematically explore barriers and facilitators affecting medication error reporting among Chinese healthcare professionals, using the Theoretical Domains Framework (TDF), a comprehensive behavioral model synthesizing 14 domains.MethodsWe conducted semi-structured interviews with 27 nurses, pharmacists, and physicians in Chinese hospitals (July-October 2024). Interviews were guided by the TDF to explore barriers to medication error reporting. Data were analyzed through framework analysis using NVivo 14.0 until thematic saturation was reached.ResultsAnalysis of semi-structured interviews explored 14 Theoretical Domains Framework (TDF) domains influencing medication error reporting among Chinese healthcare professionals, with 21 barriers and 15 facilitators delineated. Notably, eight domains emerged as predominant barriers: Knowledge, Skills, Beliefs about capabilities, Beliefs about consequences, Memory, attention and decision processes, Environmental context and resources, Social influences, and Emotion.ConclusionThis study highlights the interplay of individual, cultural, and systemic factors shaping medication error reporting in China. The TDF effectively identified context-specific barriers, including knowledge fragmentation, fear of career repercussions, and inefficient reporting systems. To foster a safety culture, interventions must integrate targeted training, simplified reporting mechanisms, and leadership commitment to non-punitive environments. Cross-professional collaboration and policy enforcement are critical to transforming reporting from a fragmented obligation into a sustainable safety practice. These insights offer a roadmap for optimizing error reporting systems in hierarchical healthcare settings globally.